2017
DOI: 10.1371/journal.pone.0175729
|View full text |Cite
|
Sign up to set email alerts
|

TRE5-A retrotransposition profiling reveals putative RNA polymerase III transcription complex binding sites on the Dictyostelium extrachromosomal rDNA element

Abstract: The amoeba Dictyostelium discoideum has a haploid genome in which two thirds of the DNA encodes proteins. Consequently, the space available for selfish mobile elements to expand without excess damage to the host genome is limited. The non-long terminal repeat retrotransposon TRE5-A maintains an active population in the D. discoideum genome and apparently adapted to this gene-dense environment by targeting positions ~47 bp upstream of tRNA genes that are devoid of protein-coding regions. Because only ~24% of tR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, similar to Ty3 elements, mutations of the box B promoter that interfere with binding of TFIIIC abolish the targeting of TRE5-A to the tRNA target gene [ 133 ]. TRE5-A insertion profiling demonstrated that TRE5-A can also integrate at the Pol III-transcribed ribosomal 5S gene which is located on a multi-copy extrachromosomal DNA element harboring the rRNA genes [ 134 , 135 ]. Unlike TRE5, TRE3 has a broader range of insertion that is 40–150 bp downstream of tRNA genes in the same transcription orientation (Fig.…”
Section: Tes Target Rna Pol III Transcribed Genes In Dictyomentioning
confidence: 99%
“…However, similar to Ty3 elements, mutations of the box B promoter that interfere with binding of TFIIIC abolish the targeting of TRE5-A to the tRNA target gene [ 133 ]. TRE5-A insertion profiling demonstrated that TRE5-A can also integrate at the Pol III-transcribed ribosomal 5S gene which is located on a multi-copy extrachromosomal DNA element harboring the rRNA genes [ 134 , 135 ]. Unlike TRE5, TRE3 has a broader range of insertion that is 40–150 bp downstream of tRNA genes in the same transcription orientation (Fig.…”
Section: Tes Target Rna Pol III Transcribed Genes In Dictyomentioning
confidence: 99%
“…Subsequently, cloning and sequencing of de novo integration sites of TRE5-A bsr revealed the authentic positioning around 50 nucleotides upstream of tRNA genes (Beck et al, 2002 ; Siol et al, 2006a ). Additionally, this construct was also instrumental to realize that, in principle, all tRNA genes can be targeted (Spaller et al, 2017 ). Whether integration alters tRNA gene expression cannot be easily investigated due to their high abundance and redundancy in D. discoideum .…”
Section: The Non-ltr Retrotransposonsmentioning
confidence: 99%
“…Unexpected TRE5-A bsr integration sites in the extrachromosomal rDNA palindrome of the amoeba (Sucgang et al, 2003 ) were also uncovered, which are characterized by perfect B box sequences (Siol et al, 2011 ). Subsequently, additional integration sites in the vicinity of the RNA polymerase III-transcribed ribosomal 5S gene were characterized (Spaller et al, 2017 ). Taken together, these data strongly point towards a general coupling of TRE5-A integration with active RNA polymerase III transcription.…”
Section: The Non-ltr Retrotransposonsmentioning
confidence: 99%